The engagement of children in out‐of‐home care with nursing and allied health professionals: A scoping review. (29th July 2021) - Hickey, Lyndal; Galvin, Karyn; Parolini, Arno; Nguyen, Bao; Lokmic‐Tomkins, Zerina; Toovey, Rachel; Skeat, Jemma; Wise, Sarah
Abstract: Background: Children living in out‐of‐home care (OOHC) have significant unmet health care needs and use more tertiary and specialist health care services compared with children from similar social and economic backgrounds. Allied health professionals and nurses have a central role in health care; however, very little is known about the engagement of children in OOHC with nursing and allied health professionals. This scoping review addresses this knowledge gap. Methods: A scoping review methodology framework was used to search for relevant articles published between January 1970 and November 2019, identified using three databases: MEDLINE, CINAHL and ProQuest. Selection of studies was based on empirical research about the health of children in OOHC and their engagement with nursing or allied health services. A total of 37 relevant articles met the eligibility criteria for inclusion in this review. Results: Findings could be summarized under five broad themes: (1) nursing and allied health professionals engaging with children in OOHC to support their health and development, (2) opportunities and challenges for nursing and allied health professionals to engage children in OOHC in healthcare, (3) identification and complexity of healthcare needs, (4) access to healthcare services and (5) coordination of healthcare. Conclusions: Children in OOHC have multiple healthcare needs that require monitoring and treatment by allied health professionals and the health and development of these children is best supported through comprehensive health screening on entry into OOHC, and community‐based, multidisciplinary healthcare while children are living in OOHC. While nurses in hospitals and community settings were found to play a role in health assessment and care coordination targeted at children in OOHC, the literature was silent on the role of allied health professionals in this healthcare approach.